The photographic subversion: Benjamin, Manet and Art(istic) reproduction - Weingarden, Lauren (Aletria: Revista de Estudos de Literatura, 2006)
Besides referring to museum masterpieces in his 1863 paintings Le déjeuner sur l’herbe and Olympia, Édouard Manet used photography, of both academic and pornographic models, new genres of commercial photography that emerged during the early 1850s. I argue that Manet deliberately conflated fine art reproductions and mass media products, a practice that invites discussion in the light of Walter Benjamin’s “The Work of Art in the Age of Its Technological Reproducibility”. Since both engaged in a dialogue with Charles Baudelaire’s writings on art, culture, and photography, these writings provide a framework for discerning modernist paradoxes inherent in Manet’s and Benjamin’s critical interpretations of popular and material culture.